General Characteristics of Sedation in Intensive Care - Yasar, Mehmet Akif (Galenos Yayincilik, 2006)
Anxiety, pain and agitation are frequently seen in patients especially who are under mechanical ventilatory support. Superficial and deep sedation have been accused of increasing complications and length of stay at intensive care units whereas on the contrary, appropriate sedation has been stated to decrease complications and length of stay at intensive care units in the contemporary literature. The aim of sedation and agents used for this purpose have differed recently. For sedation and analgesia, the American College of Critical Care Medicine (ACCM) and the Society of Critical Care Medicine (SCCM) developped a clinical practice guide and lastly published it in 2002. Determination of the level of sedation and monitorization are mandatory for these guidelines to be used. The general aims of sedation are; to control pain, anxiety and agitation, to limit the stress response, to ease the care, to increase the tolerance for endotracheal tube and to adapt to ventilatory support. The patient is aimed to be awakened more easily and to have a more comfortable stay in intensive care unit with the help of sedation and analgesia. Sedation should be applied carefully as this way alter the results of treatment in intensive care unit. Patients should be evaluated carefully to detect reversible states like hypoxia and hypercarbia which may cause agitation aims of sedation should be figured clearly objective and subjective sedation scales should be used and pharmacology of sedatives, their side effects and the effect of intensive care patients to the pharmacokinetics of these agents should be well known. The aim of this review is; to evaluate the necessity of sedation in intensive care patients and to stay away from the side effects of sedation applications while increasing their advantages to a higher level.
Keywords: sedation; intensive care unit